1994
DOI: 10.1002/cjce.5450720213
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in liquid‐filled pores of activated carbon. I. Pore volume diffusion

Abstract: The adsorption isotherms on activated carbon were measured for the following six systems: benzaldehyde, phenol, and potassium chloride in water; benzene, isopropylbenzene, and phenol in cyclohexane. The systems isopropylbenzene and benzene each in cyclohexane and potassium chloride in water proved to be slightly adsorbing systems, whereas the benzaldehyde and phenol each in water were highly adsorbing systems. The rate of diffusion of the slightly adsorbing solutes was interpreted by assuming that the intrapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 22 publications
(10 reference statements)
6
41
0
2
Order By: Relevance
“…The intraparticle diffusion can be due to pore volume diffusion, surface diffusion, or a combination of both mechanisms (Leyva-Ramos and Geankoplis, 1994;Ocampo-Pérez et al, 2010). Pore volume diffusion refers to the movement of the adsorbate due to concentration gradients in the fluid-phase (i.e., molecular mechanisms), but affected by the geometry of the porous matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The intraparticle diffusion can be due to pore volume diffusion, surface diffusion, or a combination of both mechanisms (Leyva-Ramos and Geankoplis, 1994;Ocampo-Pérez et al, 2010). Pore volume diffusion refers to the movement of the adsorbate due to concentration gradients in the fluid-phase (i.e., molecular mechanisms), but affected by the geometry of the porous matrix.…”
Section: Introductionmentioning
confidence: 99%
“…This carbon was the same one used earlier in our work on asphaltene uptakes. There have been several dye adsorption studies on activated carbons of this type as reported in the literature (Leyva-Ramos and Geankoplis, 1994, McKay and Al-Duri, 1988, Walker and Weatherley, 2001, Yang and Al-Duri, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…Para este estudio no se modificó el pH de la solución de los adsorbatos el cual estaba en un intervalo de 6,85 y 7,10, valores mayores al pHPCC, por tanto la superficie estará cargada negativamente, así que reciben la denominación de carbones L y tienen el pHPCC ˂ 7. Como se demostró experimentalmente, se observa que tanto los valores calculados con el método Boehm como los obtenidos en la determinación del pHPCC muestran que las muestras tienen mayores grupos superficiales ácidos comportamiento que se esperaba ya que fueron activas con ácido sulfúrico (Olivares-Marín et al, 2012), lo que supone que los carbones tendrán grupos oxigenados sobre su superficie, Facultad de Ingeniería − Facultad de Ciencias Básicas |23 los cuales según reportes de literatura están localizados en los bordes de las capas grafénicas, retirando la densidad electrónica de los electrones π, esto conduce a una interacción más débil entre los electrones π del anillo aromático del fenol y de las capas grafénicas, lo que podría causar un descenso en la capacidad de adsorción de los compuestos aromáticos, causando que el proceso de adsorción se efectué principalmente por las propiedades texturales sobre las propiedades químicas de los sólidos (Leyva-Ramos & Geankoplis, 1994;Moreno-Castilla, 2004;Qing-Song et al, 2010) …”
Section: Cae Cad Capunclassified